Adoption of Sharia Financial Technology and Micro, Small, and Medium Enterprises (MSME) Financial Transparency: UTAUT with Trust as a Moderator - Nazwa Syahira; Laylan Syafina; Yenni Samri Juliati Nasution (Department of Accounting, Faculty of Economics & Business, 2026)
Financial statement transparency is an important element in improving accountability and access to financing for Micro, Small, and Medium Enterprises (MSMEs), especially amid the acceleration of sharia-based financial digitalisation in Indonesia. The use of sharia fintech has the potential to encourage more accurate and transparent financial recording practices, but the factors that influence this transparency remain to be empirically tested. This study uses a quantitative approach by adopting the Unified Theory of Acceptance and Use of Technology (UTAUT) model and incorporating Trust as a moderating variable. Primary data were collected from 112 MSME actors who use sharia fintech and analyzed using Partial Least Squares–Structural Equation Modelling (PLS-SEM). The results indicate that performance expectancy, effort expectancy, social Influence, and facilitating conditions have a positive and significant effect on financial statement transparency, with facilitating conditions being the most dominant factor. Trust was found to moderate the relationship between performance expectancy and facilitating conditions on transparency, but did not play a significant role in the relationship between effort expectancy and social Influence. These findings confirm that the readiness of supporting facilities and the level of user trust are key factors in optimizing the role of sharia fintech in improving the transparency of MSME financial reports. Theoretically, this study extends the application of the UTAUT model to sharia fintech and offers practical implications for strengthening MSME financial management in the digital era.